Continuous Theta Burst Stimulation Over the Right Orbitofrontal Cortex Impairs Conscious Olfactory Perception - Villafuerte, Gabriel; Miguel-Puga, Adán; Arias-Carrión, Oscar (Frontiers in Neuroscience, 2019)
The right orbitofrontal cortex (rOFC) has been proposed as the region where conscious olfactory perception arises; however, evidence supporting this hypothesis has all been collected from neuroimaging and lesion studies in which only correlation and not a temporal pattern can be established. Continuous theta burst stimulation (cTBS) causes a reversible disruption of cortical activity and has been used successfully to disrupt orbitofrontal activity. To overcome intrinsic limitations of current experimental research, a crossover, double-blind, prospective and longitudinal study was carried out in which cTBS was applied over the rOFC to evaluate its effect on odorant stimuli detection. All subjects received real and sham cTBS. Experimental procedures were done in two different sessions with a separation of at least one week between them to avoid carryover and learning effects. A total of 15 subjects completed the experiment, and their data were included in the final analysis (10 women, 5 men, mean age 22.40 ± 3.41). Every session consisted of two different measures of the conscious olfactory perception task: A baseline measure and one 5 minutes after cTBS/sham. Compared to baseline, marks in the olfactory task during the sham cTBS session increased (p =0.010), while marks during the real cTBS session decreased (p =0.017). Our results support the hypothesis that rOFC is an important node of a complex network required for conscious olfactory perception to arise. However, the exact mechanism that explains our results is unclear and could be explained by the disruption of other cognitive functions related to the rOFC.